Reforming the European Monetary System - Manfred J. M. Neumann (Intereconomics, 1994)
The extreme widening of the exchange rate margins last summer has transformed the EMS from a multilateral fixed rate system into a system of unilateral exchange rate pegging. Professor Neumann characterises the current state of the EMS, outlines the major defects of the system and makes some proposals for reform.
Keywords: 330; European Monetary System